Phages as a Cohesive Prophylactic and Therapeutic Approach in Aquaculture Systems - Maciej Żaczek; Beata Weber-Dąbrowska; Andrzej Górski (MDPI AG, 2020)
Facing antibiotic resistance has provoked a continuously growing focus on phage therapy. Although the greatest emphasis has always been placed on phage treatment in humans, behind phage application lies a complex approach that can be usefully adopted by the food industry, from hatcheries and croplands to ready-to-eat products. Such diverse businesses require an efficient method for combating highly pathogenic bacteria since antibiotic resistance concerns every aspect of human life. Despite the vast abundance of phages on Earth, the aquatic environment has been considered their most natural habitat. Water favors multidirectional Brownian motion and increases the possibility of contact between phage particles and their bacterial hosts. As the global production of aquatic organisms has rapidly grown over the past decades, phage treatment of bacterial infections seems to be an obvious and promising solution in this market sector. Pathogenic bacteria, such as Aeromonas and Vibrio, have already proved to be responsible for mass mortalities in aquatic systems, resulting in economic losses. The main objective of this work is to summarize, from a scientific and industry perspective, the recent data regarding phage application in the form of targeted probiotics and therapeutic agents in aquaculture niches.